Polypoid endometriosis in a young female with systemic lupus erythematosus, mimicking ovarian and pelvic malignancy, a case report - Yu-Min Fan; Tao-Yeuan Wang; Jen-Ruei Chen (Taiwanese Journal of Obstetrics & Gynecology)
Objective: Polypoid endometriosis is a rare mass-like variant of endometriosis. Mass-like content with indistinct margins between the uterus and pelvic side wall mimics characteristics of pelvic malignancy. Systemic lupus erythematosus (SLE) has also been associated with higher incidences of endometriosis. However, SLE cases with polypoid endometriosis have never been reported in English literature. Case report: A 33-year-old female presented with SLE and polypoid endometriosis. Initially, she received a left salpingo-oophorectomy due to suspicion of ovarian malignancy, but only endometrioma with polypoid feature was diagnosed. Repeated second surgery was conducted because of a new-growth complex mass between the uterus and the pelvic side wall, causing myometrial invasion and left hydroureter/hydronephrosis. Finally, polypoid endometriosis of the pelvic side wall was diagnosed pathologically. Conclusion: Polypoid endometriosis is still a diagnostic challenge before pathological confirmation. This case of SLE and polypoid endometriosis may be the first reported worldwide.